The Role of the Madiun City Goods and Services Procurement Work Unit (UKPBJ) in Accelerating Development and Public Services from a Legal Perspective - Septiana Widya Handayani; Faturrahman; Sarjiyati; Sigit Sapto Nugroho (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: Government procurement of goods and services plays a crucial role in development implementation, as well as serving as a manifestation of good governance and an indicator of the quality of public service performance. Therefore, the Madiun City Goods/Services Procurement Work Unit (UKPBJ) was established and established to carry out procurement of goods and services professionally. Purpose/Study Objectives: The purpose of this study is to analyze the role of the Madiun City Goods and Services Procurement Work Unit (UKPBJ) in accelerating development and public services through government procurement of goods/services and to analyze the obstacles or constraints faced in the implementation of Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods and Services as amended by Presidential Regulation Number 12 of 2021 on the Madiun City UKPBJ and how to solve them. Design/Methodology/Approach: The research method used in this research is empirical juridical, data sources are primary data in the form of observations, interviews and document studies while secondary data are in the form of books, journals, reports, etc. The data analysis uses qualitative analysis methods. Findings: The results of the study show that the role of the Madiun City Goods and Services Procurement Work Unit (UKPBJ) in accelerating development and public services includes: (1) Management of Goods/Services Procurement, (2) Management of Electronic Procurement Services (LPSE), (3) Development of Human Resources (HR) and Institutional Procurement of Goods/Services (PBJ), (4) Mentoring, Consultation, and Technical Guidance, (5) Implementing other tasks. While internal obstacles are: (1) Lack of human resources (HR) for Functional Positions of Goods/Services Procurement Managers, the solution is to apply for recruitment either through the selection path for State Civil Apparatus Candidates (CASN) or through transfer of positions for ASN in other functional positions, (2) Obligation of Goods and Services Procurement Officials (PPBJ) to be certified, the solution is to follow education and training according to the required standards. Meanwhile, externally, namely: (1) Not following and mastering the dynamics of legal regulations, the solution is to follow technical guidance and training. (2) Gaptek (Technology Ignorance) in Procurement of Goods and Services, the solutions include: (1) Education and Training, (2) Use of Digital Systems, (3) Technical Support Systems, (4) Improving Internet Access. Paper Type: Research Article